KEMATANGAN BERAGAMA DAN SIKAP TASAMUH MARGA MASYARAKAT ACEH DI ACEH SINGKIL - Sakdiah Sakdiah (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2020)
The people in Aceh Singkil Regency are very heterogeneous, including ethnicity, clan, religion, where this condition tends to cause various frictions in the community. In maintaining integrity and harmony amid community diversity, religious maturity and the attitude of the tasamuh marga of the Aceh Singkil community are social glue and kinship relations that dilute the atmosphere of inter-religious disputes in solving various problems in society. Fostering an attitude of intolerance and mutual respect through psycho, social, cultural, and religious approaches. Where every small friction will be reduced so as not to cause big problems. This research reveals problems that will be described by (1) Religious maturity and the attitude of tasamuh clans of the Acehnese people in Singkil. (2). Supporting factors and obstacles to religious maturity and the attitudes of the community in Aceh Singkil. Marga has tightened the ties of friendship and tasamuh in religion to the people of Aceh Singkil, marga has helped to cut religious problems that have arisen due to the destroyed houses of worship, marga has made social relations of blood kinship closer despite different religions in the Aceh Singkil community.           Key words: maturity, tasamuh marga, Aceh Singkil